Non-linear dynamic analysis of arch dams using drucker-prager approach - Calayir, Yusuf; Karaton, Muhammet (My University, 2004)
In this study, the effects of the material non-linearity of concrete on the dynamic response of arch dams are investigated. Drucker-Prager approach is selected for non-linear model of the dam concrete material. Dam-reservoir and dam-foundation interaction effects are considered in the dynamic analysis. Finite element formulation of dynamic fluid-structure interaction problem is given by using the Eulerian approach. For numerical application, linear and non-linear dynamic analyses of Karakaya arch dam are performed. The eservoir and the foundation domains are assumed as linear elastic. For the dynamic input, the S69E component of 21 July 1952 Taft earthquake is used as the horizontal component, acting in the downstream-upstream direction of the dam. Linear and non-linear dynamic solutions of the Karakaya arch dam are obtained and the results are compared with each other. Damage regions on the dam body occurred by the effects of earthquake ground motion are determined.
Kemer Barajlain Drucker-Prager Yaklaşimi Kullanilarak Lineer Olmayan Dinamik Analizi
Keywords: Concretes; Dynamic response; Dynamics; Earthquake effects; Finite element method; Reservoirs (water); Dam concrete materials; Drucker-Prager Approach; Dynamic analysis; Karakaya arch dam; Arch dams